Sars-CoV-2 infection in patients with cystic fibrosis. An overwiew - Fainardi, Valentina; Longo, Francesco; Chetta, Alfredo; Esposito, Susanna; Pisi, Giovanna (Acta Biomedica Atenei Parmensis, 2020)
The novel coronavirus SARS-CoV-2 was first identified in China in December 2019 and has since spread worldwide. People with Cystic Fibrosis (CF) have reduced survival mainly because of respiratory failure due to chronic pulmonary infections. Therefore, CF patients should be considered to have an increased risk of developing severe manifestations in case of SARS-CoV-2 infection. Surprisingly, the results of recent studies concerning SARS-CoV-2 infection in patients with CF show that in these patients the infection rate was lower than that of the general population. Various factors have been considered to explain a possible protective effect of CF against SARS-CoV-2 infection.